Supply Chain Networks and Business Process Orientation: Advanced Strategies and Best Practices - McCormack, Kevin (CRC Press, 2009)
With future competitive landscape shifting from competition between companies themselves to trading partner networks, understanding and mastering process design and change is becoming more critical than ever. In order to succeed, companies are starting to weave their key business processes into hard-to-imitate strategic capabilities that distinguish them from their competitors. Supply Chain Networks and Business Process Orientation: Advanced Strategies and Best Practices will help you "connect the dots" by offering insights on how to achieve greater integration within your supply chain networks and realize the performance possible with today's interaction economics.